Conceptualising teacher resilience: A comparative systematic multidisciplinary review of teacher resilience literature - Subosa, MR (2021)
Background – Substantive research into teacher resilience has focused on a variety of individual and contextual factors that hinder or help teachers to overcome challenging situations in the exercise of their profession. Rooted primarily in psychological theories, extant teacher resilience literature has largely focused on personal dispositions, social relations, and school processes, with little attention to cultural and structural factors that affect teachers’ work. Comparative, cross-country analysis has also been limited.